Estudio del Testamento y Codicilos del Inca Garcilaso de la Vega: Primer Humanista Peruano (a. 1616) - De la fuente, Rosario (Revista de Derecho, 2019)
The present work presents the last will of Gómez Suárez de Figueroa, Inca Garcilaso de la Vega, first Peruvian humanist, through the testaments and codicils written in 1616, the last year of his life, and which were found by record keeper Ricardo Gómez y Sánchez in the protocols files of the Cathedral of Córdoba, along with the inventory of assets and a memorial, being published more than a Century ago, in 1908, by Manuel González de la Rosa, but which lack a study from a juridical point of view.Along its analysis attention is drawn to its formal similarity to testamentary models registered starting in the first half of the 17th Century, as well as to its peculiarities in terms of content, to then close with its transcription.
Keywords: Inca Garcilaso de la Vega; humanism; testament; codicil; ejecutor; piae causae; inheritance; legacies,; census; foundation; chaplaincy